Banking with Very Poor Women: Outreach and Sustainability of CARD-Rural Bank, a Grameen Innovator in the Philippines - Hans Dieter Seibel (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 1999)
The Grameen Bank in Bangladesh is known worldwide for its success in providing credit to the poor. However, subsequent replications of its methodology in other parts of the world have been less successful. Is there really an infallible solution that works everywhere, and is outreach to the poor compatible with sustainability? A Grameen replic ator in the Philippines, the Center for Agriculture and Rural Development (CARD), has recently set itself firmly on the path to sustainability through becoming a formal sector, rural bank – the first credit NGO in the country to do so. During the period 1993 to June 1999, CARD?s all-female outreach soared from 1,711 to 26,369 and its operational self-sufficiency ratio increased from 0.46 to l.09. At the end of June 1999, CARD?s loan portfolio stood at 2.7 million, its repayment rate was 99.9 per cent and its financial self-sufficiency ratio was 0.85. The principal lesson to be learned from CARD?s success is that Grameen-type MFIs can be sustainable and can substantially increase their outreach. CARD?s social capital comprises: (a) a core of good Grameen practices, such as high moral commitment on the part of the leaders, based on values instilled through training; peer control – to preclude adverse selection and moral hazard; and a strict credit discipline; (b) innovative adaptations to suit the Philippine context, such as the adoption of rural bank status under central bank supervision; vigorous mobilization of voluntary savings; the provision of differentiated, profit-making loan and insurance products; and a broadening of the clientele to include poor and non-poor depositors, while adhering to its mission of lending to poor women only.
Keywords: 330